Performance Investigation of Tunnel Lining with Cavities around Surrounding Rocks - Jiajia Li; Yong Fang; Cheng Liu; Yongxing Zhang; Weihua Lu (Advances in Civil Engineering)
This paper presents a systematical numerical investigation into the lining performance of a tunnel with cavities around surrounding rocks, focusing on the influences of cavity size and multicavity distribution. The study demonstrates that the cavities around surrounding rocks have much influence on tunnel stability and may induce damages in tunnel structures, in which cavity width has a more severe effect on the stress state of tunnel structures than cavity depth. Moreover, the numerical investigation also illustrates that the nonadjacent distribution of multicavities has more serious influence on tunnel structures than that from adjacent distribution of multicavities as well as that from a single cavity.